Conductivity and Structure of Superionic Composite (AgI)0.6(NaPO3)0.4 - E Kartini; T Sakuma; A Purwanto; T Kamiyama; MF Collins (PPIKSN-BATAN, 2005)
Superionic conductors are of considerable interest from both application and fundamental points of view. Superionic solid electrolytes can be used for batteries, fuel cells and sensors. We have used melt quenching to make a new superionic composite (AgI)0.6(NaPO3)0.4 which exhibits an ionic conductivity of about 2 x 10-4 S/cm at ambient temperature. The conductivity of crystalline AgI and NaPO3 glass are lower of orders of magnitude. (AgI)0.6(NaPO3)0.4 is a composite material containing both crystalline and glass phases. The paper presents the conductivity as a function of temperature measured by impedance spectroscopy and the crystal structure performed by a high resolution powder diffractometer, VEGA at the Neutron Science Laboratory (KENS), KEK, Japan.